An investigation of impacts that a partially non-integrated computerized accounting system cause on financial reporting in local authorities: case Study of Chiredzi Town Council - Zivanai, Tapiwanashe (Midlands State University, 2017)
The Computerized Accounting System (C.A.S) is of extreme importance in providing the financial information for decision making purposes within the organization. The research is about the impact that a Partially Non-Integrated Computerized Accounting System causes on Financial Reporting in Local authorities. For the past years Chiredzi Town Council has been facing challenges due to the operation of Non-Integrated CAS. The Local Authority used three different accounting packages which are Pastel, PROMUN and ADASK. The organization was facing risks such as data manipulation, errors and perpetration of frauds by the system users taking advantage of the weak system and this resulted in poor decision making. There was also delayed financial reporting which was caused mainly by the company’s accounting system. The research showed that the degree of Non-Integrated AIS was very high at the organization though integrated systems Enterprise Resource Planning (ERP) were in place. To reduce the risks the company was encouraged to use fully Integrated Accounting software for example PROMUN alone. There was also encouragement for management to put more supervision on the staff, motivation of staff and consistence in training of staff to have skills and experience on new versions of the accounting software.